2019
DOI: 10.1039/c9ra06491e
|View full text |Cite
|
Sign up to set email alerts
|

d-Glucose sensor based on ZnO·V2O5 NRs by an enzyme-free electrochemical approach

Abstract: A simple wet-chemical technique was used to prepare zinc oxide-doped vanadium pentaoxide nanorods (ZnO·V2O5 NRs) in an alkaline environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Glucose is converted to gluconolactone and finally to gluconic acid with the release of H 2 O 2 . The H 2 O 2 decomposes into an oxygen molecule and protons by generating electrons which are responsible for the current-potential characteristic for glucose sensing [ 33 ]. The glucose-sensing phenomenon is well elaborated in the following reactions: …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Glucose is converted to gluconolactone and finally to gluconic acid with the release of H 2 O 2 . The H 2 O 2 decomposes into an oxygen molecule and protons by generating electrons which are responsible for the current-potential characteristic for glucose sensing [ 33 ]. The glucose-sensing phenomenon is well elaborated in the following reactions: …”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, two cathodic peaks were observed with one considerably below −100 mV and the other slightly above 600 mV. However, a calibrated potential higher than the latter was selected to construct the calibration curve because detection of enzymatic reaction (oxidation of H 2 O 2 ) takes place at 600 mV at Pt electrode [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOQ was found for GABA (39.0 pM) and TST (322.2 pM) from calibration curves based on eqn (x)-(xii). [19][20][21][22][23] Where, m ¼ slope of the calibration bend (1 Â 10 À5 and 9 Â 10 À5 ), A ¼ dynamic surface area of GCE (diameter ¼ 0.0316 cm 2 ), SD ¼ standard deviation (0.39 and 0.29) of GABA and TST concentration, calibrated at +0.6 V (Fig. 5b-d).…”
Section: Assessment Of Binding Energies Using Xps Experimentsmentioning
confidence: 99%
“…A xed quantity ($25.0 mL) of each natural sample was examined in phosphate buffer (10.0 mL, pH ¼ 7.5, and 100.0 mM) using the modied BDMMBSH/GCE/NF sensor. [43][44][45][46][47][48][49] The concentrations were calculated at the calibrated potential (+0.7 V) for the detection of Pb 2+ in coal water, industrial effluent, Red Sea water, rice water, tap water, and well water, which absolutely demonstrated that the I-V method is proper, reliable, and appropriate for the analysis of real samples. Fig.…”
Section: Analysis Of Real Environmental Samplesmentioning
confidence: 99%